Marburg virus in Rwanda: challenges, strategies, and future directions - Majani Edward (Discover Public Health)
Abstract Rwanda is currently facing its first-ever Marburg virus outbreak, a deadly zoonotic disease with a high fatality rate. As of September 2024, the virus has spread across seven districts, with 26 confirmed cases and six fatalities. This article examines Rwanda’s response to the outbreak, highlighting government-led efforts such as isolation of cases, contact tracing, and community awareness campaigns. Additionally, the role of the World Health Organization (WHO) and other international organizations in providing emergency medical supplies and expertise is discussed. The article emphasizes the importance of robust public health infrastructure, noting that while Rwanda's emergency systems have been effective, there is a need to enhance early detection and laboratory capacity. Looking ahead, recommendations are provided for strengthening Rwanda’s preparedness against future outbreaks. These include improving surveillance systems, participating in global vaccine and treatment development, and fostering cross-border collaborations to prevent regional spread. The importance of community engagement is underscored, as public trust in health authorities is vital for successful outbreak containment. Ultimately, while Rwanda’s response to the Marburg virus has been commendable, sustained investment in healthcare systems and international partnerships will be essential for long-term resilience against future public health threats.